Plan de negocios para la creación de una distribuidora y comercializadora de bebidas alcohólicas en el municipio de Pivijay Magdalena (2022)
This business idea is carried out in order to study the viability and profitability of a distributor and marketer of alcoholic beverages in the municipality of Pivijay Magdalena. This research began when detecting the need of the population and the increase in the levels of sale of these products over the years. In addition, bearing in mind that, within the scope of application of innovation management, what is sought is the generation and production of innovative ideas, which can be implemented and generate continuous value as well as the local context of operation. The implementation of this distributor and marketer would represent an improvement in many areas in terms of the economy of the municipality, as it will be a job opportunity for peoplewho are part of the company, as well as ensuring a good supply of liquors at the headquarters and also in the surrounding villages where strategic points will be placed to be able to cover the existing demand. This project is part of a mixed research, with the purpose of collecting both qualitatives and quantitatives datas. In addition to this, it follows institutional guidelines, based on a line of research called innovation management, which is subdivided in this case into social innovation. All of the above will allow us to identify, to a great extent, whether the business idea to be launched in the municipality of Pivijay Magdalena will be profitable.